The Analysis of Dimensional Changes and The Number of Simple Composite Girder Dimoro Bridge On The Southern Coast Access In Malang East Java - Edy Gardjito (International Conference on Coastal and Delta Areas, 2017)
Accelerated development of cross-coastal access to southern eastern Java, known as the South Coast Cross Lane (JLS) very dependent with the topography of the southern region of Java island, about 65% of JLS are in mountainous and coastal areas. One of them is the construction of Dimoro Bridge in Malang East Java region with simple composite girder type spans 20.00 meters. According to basic design, girder dimensions use IWF. 980 x 350 x 10 x 35, with the number of girder n = 7 and the girder length 20.40 m. The issue of girder dimensions IWF. 980 x 350 x 10 x 35 is not mass-produced by the steel industry, so there needs to be a design review with the dimensions of girder in the steel industry market with IWF. 800 x 300 x 14 x 26. The analysis of dimensional changes and the number of simple composite girder is reviewed from : (1) the height of the girder profile approaching plan (d), because when the smallest (d) value is taken there will be more number of girder (n) installed. (2) the weight of the bridge structural steel approaching plan (Wr), since if Wr' < Wr means fulfilled by not changing the calculation of the bridge foundation, if Wr' > Wr then it is necessary to recalculate the strength of the bridge foundation. Analyze results for bending moments on IWF girder. 800 x 300 x 14 x 26 is obtained : M precomposite = 43850 kg.cm, M post-composite = 13816200 kg.cm. The moment of resistance (wb) due to Mpre and Mpost = 5003 cm3. Moment of inertia (Ix) = 282554 cm4 (table Ix = 292000 cm4). The moment of resistance (wx) = 7064 cm3 (table wx = 7290 cm3). Control of ultimate stress σau* = 2780 kg/cm2 is obtained Mmax = 12030000 kg.cm, σa' = Mmax/wx = 2405 kg/cm2 > σa = 1850 kg/cm2, the stress σa' exceeds the permit stress σa but still below ultimate stress σau* (safe). Control of deflection, for L/250 obtained Ix = 157733 cm4 < Ix plan = 282554 cm4 (safe). For L/360 obtained Ix = 201819 cm4 < Ix plan = 282554 cm4 (safe). Control of the shear stress obtained T = 229.76 kg.cm2 <T'= 0.58xσa = 0.58 x 1850 = 1073 kg.cm2 (safe). Control of tensile stress and press on composite girder, compressive stress σsu = 389.7 kg/cm2 < σa = 1850 kg/cm2 (safe), tensile stress σsl = 1123.3 kg/cm2 < σa = 1850 kg/cm2 (safe). Preferred on the composite girder is the compressive stress (σsu), and the resulting compressive stress (σsu) after the composite is smaller than the allowable stress (σa = 1850 kg/cm2; σau* = 2780 kg/cm2), the dimensional change IWF girder being 800 x 300 x 14 x 26 is safe to use. The change of girder number to IWF 800 x 300 x 14 x 26, profile area F = 261 cm2 (table F = 267 cm2), girder weight per m wt1 = 261x0.785 = 205.00 kg/m' (table = 210.00 kg/m'), weight 1 girder Wt(p) = 4100 kg. Needs of girder n'= Wt7/Wt(p) = 9.40 → taken 9 girder, Wt9 = 36900 kg < Wt plan = 38556 kg (ok). Accessories on the composite girder include : connection plate + bolt, diaphragm (bracing iron elbow) + bolt, shear-connector. Total weight of Accessories 9 girder = (3692+215+737) = 4644 kg. Total weight of composite bridge steel structure 9 girder Wr = 36900+4644 = 41544 kg < weight plan Wr = 41635 kg (fulfilled by not changing bridge foundation calculation). Keywords: pre-composite moment, post-composite moment, ultimate stress, deflection, shear stress.